Appropriateness of diagnostics tests. (9th May 2016) - Cappelletti, P.
Summary: The evolution of the concept of 'appropriateness', in the three past decades, from 'no harm' and 'no waste' to 'medical decision‐making' and 'determining outcomes' highlights two main points: its foundation is evidence‐based medicine, and it is a quality of every phase of the total testing process, not only for the selection of tests. Nevertheless, appropriateness in Laboratory Hematology, as well as in Laboratory Medicine, is an elusive concept: 'Appropriateness' interplays with 'patient's safety', 'healthcare costs', 'clinical decision‐making', and 'effectiveness', and the criteria for appropriateness, mainly adherence to clinical guidelines, are often not evidence‐based and not always consensus‐based. Moreover, practising appropriateness is a complex issue because of the ambiguity of the criteria and targets, the never‐ending work of implementing guidelines and their audit, and the uniqueness of the clinical situation of the individual patient. Authors agree on some practical rules: establishing a multidisciplinary and multiprofessional team, choosing carefully clinical targets, finding or building evidences, sharing guidelines with clinicians, choosing adequate tools for changing, working hard on implementation, identifying the 'right' laboratory methods and processes, checking progress indefinitely, providing information, interpretations, and consultations, and promoting feedback and audits. The success depends on the 'right' combination of educational, operative, and reinforcing interventions. Competences in organization, in implementation science, and in interpersonal relationship management are essential as well as knowledge and experience in Hematology, not only in Laboratory Hematology.